2018
DOI: 10.1155/2018/9834059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gabapentinoids Premedication on Shoulder Pain and Rehabilitation Quality after Laparoscopic Cholecystectomy: Pregabalin versus Gabapentin

Abstract: Introduction Gabapentinoids are increasingly used in preoperative premedication despite controversial results. The aim of our study was to evaluate the effects of preemptive use of gabapentin or pregabalin on postoperative shoulder pain and rehabilitation quality after laparoscopic cholecystectomy. Methods This is a clinical trial comparing the effects of a preoperative premedication with 600 mg of gabapentin or 150 mg of pregabalin versus placebo on postoperative pain and recovery quality after laparoscopic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…Zaliczanymi do tej grupy substancjami są gabapentyna i pregabalina. Gabapentyna podawana w dawce 1200 mg przed zabiegiem operacyjnym zmniejsza natężenie bólu odczuwane przez pacjenta [40,41] oraz obniża zapotrzebowanie na opioidy w okresie pooperacyjnym. Gabapentyna stosowana z morfiną zmniejsza efekty uboczne związane z przyjmowaniem opioidów, tj.…”
Section: Leki Przeciwbóloweunclassified
See 1 more Smart Citation
“…Zaliczanymi do tej grupy substancjami są gabapentyna i pregabalina. Gabapentyna podawana w dawce 1200 mg przed zabiegiem operacyjnym zmniejsza natężenie bólu odczuwane przez pacjenta [40,41] oraz obniża zapotrzebowanie na opioidy w okresie pooperacyjnym. Gabapentyna stosowana z morfiną zmniejsza efekty uboczne związane z przyjmowaniem opioidów, tj.…”
Section: Leki Przeciwbóloweunclassified
“…Gabapentyna stosowana z morfiną zmniejsza efekty uboczne związane z przyjmowaniem opioidów, tj. nudności, wymioty [41][42][43][44], oraz zmniejsza incydenty zatrzymania moczu [45]. Aplikowana w dawce 600 mg według danych eksperymentalnych niestety nie wpływa na zmniejszenie zapotrzebowania na leki przeciwbólowe [44,46].…”
Section: Leki Przeciwbóloweunclassified
“…In a more recent meta-analysis that included 43 studies, they also reported reduction in analgesic usage associated with perioperative pregabalin usage [13]. One placebo-controlled RCT demonstrated no analgesic superiority between gabapentin (600 mg) and pregabalin (150 mg) during the first 48 postoperative hours following laparoscopic cholecystectomy in terms of postoperative shoulder pain, although it failed to evaluate opioid consumption [14]. In contrast, another RCT involving lumbar spine surgery showed improved postoperative opioid consumption for preoperative pregabalin in comparison to gabapentin [15].…”
Section: Pregabalinmentioning
confidence: 99%
“…There are few studies on effect of Gabapentin on acute post-operative pain control in laparoscopic cholecystectomy. 9,10 Aim of present study was to evaluate efficacy of oral Gabapentin in relief of acute post-operative pain in laparoscopic cholecystectomy and also compare the efficacy of oral Gabapentin with that of oral Tramadol. This study was conducted in the Department of anesthesiology and intensive care unit of the hospital.…”
Section: Introductionmentioning
confidence: 99%